Utilization of surimi-like products from pork with sex-odor in restructured, precooked pork roasts - C M Garcia Zepeda; Curtis L Kastner; Melvin C Hunt; P B Kenney; J R Schwenke; D S Schleusener; Donald H Kropf (Kansas Agricultural Experiment Station Research Reports, 1990)
Surimi-like materials from boar and sow muscle and Alaska pollack surimi were evaluated at a 5% inclusion level in a restructured, precooked (158Â°F) pork roast. Meat batches were formulated to contain 95% chunked ham muscles and either 5 or 0% surimi-like or surimi binder, either 0.2 or 1.0% NaCl, and 0.5% phosphate. The surimi washing process did not remove or decrease boar taint intensity of the binder or enhance instrumental and sensory textural characteristics of the finished product. Products without binder were comparable or superior in textural and microbial characteristics to those with binders. Increasing salt content had detrimental effects on TBA (rancidity) and color but enhanced product textural attributes. Fish surimi did not have greater structural integrity than washed boar counterparts.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; Boar; Odor; Pork; Quality